2005
DOI: 10.1177/0885066605279834
|View full text |Cite
|
Sign up to set email alerts
|

In Acute Organophosphate Poisoning, the Efficacy of Hemoperfusion on Clinical Status and Mortality

Abstract: The aims of this study were to report experience in patients with organophosphate poisoning (OPP) and to discuss the potential role for hemoperfusion (HP) in the management of severe OPP. At the emergency service of a university hospital, 52 patients with acute OPP were included in this retrospective study. The patients were divided into 2 groups (Group 1, severe poisoning, n = 25; and Group 2, mild poisoning, n = 27). All patients with mild OPP survived. Seven patients (28%) of the 25 with severe OPP died. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Two meta-analyses [5,28] , as well as two systematic reviews [6,29] and a Cochrane review [30] evaluating the role of oximes in OP poisoning were also identified. In addition, one prospective trial each on magnesium [31] and fresh frosen plasma therapy [32] , two trials on haemoperfusion [33,34] , as well as a Cochrane systematic review on the role of alkalinisation in human OP poisoning [35] were identified. The physiological basis of each of these therapies as available from animal and experimental data was also reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two meta-analyses [5,28] , as well as two systematic reviews [6,29] and a Cochrane review [30] evaluating the role of oximes in OP poisoning were also identified. In addition, one prospective trial each on magnesium [31] and fresh frosen plasma therapy [32] , two trials on haemoperfusion [33,34] , as well as a Cochrane systematic review on the role of alkalinisation in human OP poisoning [35] were identified. The physiological basis of each of these therapies as available from animal and experimental data was also reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Although Peng et al [34] , in the prospective evaluation, demonstrated benefits with haemoperfusion, Altintop et al . [33] found more deaths in a retrospective cohort that underwent haemoperfusion. However, the crucial factor determining response, again as with oximes, may be the time of provision of haemoperfusion.…”
Section: Adjunct Therapymentioning
confidence: 93%
See 2 more Smart Citations
“…As reported in the literature (2,5,20,21) It is described in literature that OP poisoning is an important cause of mortality and morbidity (6,23,24). Yurumez et al (17) and Seydaoglu (21) It is said that necrotizing pancreatitis (25), coital-like involuntary movements (26) and intermediary syndrome may develop in patients after OP poisoning (27,28).…”
Section: Methodsmentioning
confidence: 99%